Synthesis and Tyrosinase Inhibitory Activity of (E)-5-Benzyl-7- (3-Bromobenzylidene)-3-(3-Bromophenyl)-2-Phenyl-3,3a, 4,5,6,7-Hexahydro-2H-Pyrazolo[4,3-c]Pyridine - Nelly Oscifiani; Noval Herfindo; Rahayu Rahayu; Neni Frimayanti; Adel Zamri (Jurnal Kimia Sains dan Aplikasi, 2022)
The tyrosinase enzyme plays an essential role in the pigmentation of human skin, fruits, and vegetables. It has been tied with several human skin diseases and post-harvest problems. Hence, the tyrosinase enzyme becomes an excellent therapeutic target to overcome these issues. This study aimed to screen tyrosinase inhibitors by synthesizing halogen-substituted pyrazolopyridine derivatives. The pyrazolopyridine compound was obtained through two stages of synthesis. First, the intermediate compound, a derivative of 3,5-bis(arylidene)-4-piperidone, was synthesized through the Cleisen-Schmidt condensation reaction of 4-piperidone and benzaldehyde derivatives. Furthermore, the intermediate compound was reacted with phenylhydrazine through a cyclocondensation reaction to produce the titled compound with an 11% yield. The chemical structure of the target compound was identified through the interpretation of UV, FTIR, NMR, and HRMS spectra. Then an in vitro assay was conducted on the tyrosinase enzyme of the fungus Agaricus bisporus by detecting the presence of dopachrome at a wavelength of 492 nm. As a result, the in vitro assay showed that the titled compound had a weak inhibitory activity, and the IC50 value was > 500 µM. Thus, the synthesized compound is considered inactive.